The redox cycler plasmodione is a fast-acting antimalarial lead compound with pronounced activity against sexual and early asexual blood-stage parasites - Ehrhardt, Katharina; Deregnaucourt, Christiane; Goetz, Alice-Anne; Tzanova, Tzvetomira; Gallo, Valentina; Arese, Paolo; Pradines, Bruno; Adjalley, Sophie H.; Bagrel, Denyse; Blandin, Stephanie; Lanzer, Michael; Davioud-Charvet, Elisabeth (Antimicrobial agents and chemotherapy, 2016)
Previously, we presented the chemical design of a promising series of antimalarial agents, 3-[substituted-benzyl]-menadiones, with potent in vitro and in vivo activities. Ongoing studies on the mode of action of antimalarial 3-[substituted-benzyl]-menadiones revealed that these agents disturb the redox balance of the parasitized erythrocyte by acting as redox cyclers—a strategy that is broadly recognized for the development of new antimalarial agents. Here we report a detailed parasitological characterization of the in vitro activity profile of the lead compound 3-[4-(trifluoromethyl)benzyl]-menadione 1c (henceforth called plasmodione) against intraerythrocytic stages of the human malaria parasite Plasmodium falciparum. We show that plasmodione acts rapidly against asexual blood stages, thereby disrupting the clinically relevant intraerythrocytic life cycle of the parasite, and furthermore has potent activity against early gametocytes. The lead's antiplasmodial activity was unaffected by the most common mechanisms of resistance to clinically used antimalarials. Moreover, plasmodione has a low potential to induce drug resistance and a high killing speed, as observed by culturing parasites under continuous drug pressure. Drug interactions with licensed antimalarial drugs were also established using the fixed-ratio isobologram method. Initial toxicological profiling suggests that plasmodione is a safe agent for possible human use. Our studies identify plasmodione as a promising antimalarial lead compound and strongly support the future development of redox-active benzylmenadiones as antimalarial agents.
Gesehen am 05.05.2020